A Randomized Phase III Study of Abemaciclib Versus Erlotinib in Patients with Stage IV Non-small Cell Lung Cancer With a Detectable KRAS Mutation Who Failed Prior Platinum-Based Therapy: JUNIPER - Goldman, Jonathan W.; Mazieres, Julien; Barlesi, Fabrice; Dragnev, Konstantin H.; Koczywas, Marianna; Göskel, Tuncay; Cortot, Alexis B.; Girard, Nicolas; Wesseler, Claas; Bischoff, Helge; Nadal, Ernest; Park, Keunchil; et al. (Frontiers in Oncology, 2020)
Introduction: JUNIPER compared the efficacy and safety of abemaciclib, a selective cyclin-dependent kinase 4 and 6 inhibitor, with erlotinib in patients with non-small cell lung cancer (NSCLC) harboring a Kirsten rat sarcoma (KRAS) mutation. Methods: JUNIPER was a Phase III, multicenter, randomized, open-label trial of abemaciclib versus erlotinib in patients with stage IV NSCLC and a detectable mutation in codons 12 or 13 of the KRAS oncogene, who progressed after platinum-based chemotherapy and 1 additional therapy (could include immune checkpoint inhibitor therapy). Randomized patients (3:2) received either 200 mg abemaciclib twice daily or 150 mg erlotinib once daily with best supportive care until disease progression or unacceptable toxicity. The primary endpoint was overall survival (OS); secondary endpoints included overall response rate (ORR), progression-free survival (PFS), and safety. Results: Between Dec 2014 and Apr 2017, 453 patients were randomly assigned to receive abemaciclib (N=270) or erlotinib (N=183). Median OS was 7.4 months (95% confidence interval [CI]: 6.5, 8.8) with abemaciclib and 7.8 months (95% CI: 6.4, 9.5) with erlotinib (hazard ratio [HR]=0.968 [95% CI: 0.768, 1.219]; p=.77). Median PFS was 3.6 months (95% CI: 2.8, 3.8) with abemaciclib and 1.9 months (95% CI: 1.9, 2.0) with erlotinib (HR=0.583 [95% CI: 0.470, 0.723]; p<.000001). ORR was 8.9% and 2.7% (p=.010) and the disease control rate was 54.4% and 31.7% (p<.001) with abemaciclib and erlotinib, respectively. Safety results reflected the known safety profiles of abemaciclib and erlotinib. Conclusions: In this study, the primary endpoint of OS was not met; PFS and ORR were improved with manageable toxicity in the abemaciclib arm. The increases in response rates and PFS support further investigation of abemaciclib in other NSCLC subpopulations or in combination with other agents.